Shock & vibration, aircraft/aerospace, energy harvesting, acoustics & optics. proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 /: proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017. Volume 9 : (2017) - Unknown
No abstract available